Evidences of Seasonal Aggregations and Breaching Behaviour of Blacktip (Carcharhinus limbatus) and Spinner (C. brevipinna) Sharks in a Southwest Atlantic Marine Protected Area - Rolim, Fernanda Andreoli [UNESP]; Rodrigues, Pedro Furtado Costa [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP]; dos Santos Motta, Fábio; Slerca, Marco Antonio Light; Araujo, Nathan Lagares Franco; Neves, Leonardo Mitrano (Wiley, 2025)
ABSTRACT This study indicates a seasonal aggregation behaviour in Blacktip ( Carcharhinus limbatus ) and Spinner ( C. brevipinna ) sharks over 6 years of data in Ilha Grande Bay, a warm temperate bay in Rio de Janeiro, Brazil. Observations from visual surveys, drone footage and Baited Remote Underwater Video (BRUV) deployments revealed mixed‐species aggregations, reaching a maximum of 113 individuals, and recorded the first instances of breaching behaviour of sharks in the Southwest Atlantic. These aggregations occurred seasonally during austral autumn and winter in a shallow cove near a nuclear power plant, partially within a no‐take marine protected area. Understanding these behaviours provides valuable insights for effective management and conservation strategies in the region.